Contractual Solidarity in Iranian Civil Law - S. Mohammadi; J. Yahyapour (مطالعات فقه و حقوق اسلامی, 2011)
Abstract According to article 698 of civil code, by making guaranty contract, the obligation of the (original) debtor is discharged and the obligation of the guarantor towards the creditor (guarantee), comes into force. Although under the mentioned article, the guaranty contracts causes the transfer of obligation, but with regard to prevailing custom on guaranty (solidarity) and the necessity of using the words of contracts in custom purport, we can consider the transfer of obligation out of essence of the guaranty contract and any stipulation contrary to it as good (valid). Therefore in the custom viewpoint, the guaranty causes longitudinal solidarity i.e. arter the contract, guaranteed, remains as original debtor and the guarantor is responsible to pigment similar to a security.